2022
DOI: 10.3174/ajnr.a7664
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Synthetic MRI with Deep Learning–Based Reconstruction for Pediatric Neuroimaging

Abstract: BACKGROUND AND PURPOSE: Synthetic MR imaging is a time-efficient technique. However, its rather long scan time can be challenging for children. This study aimed to evaluate the clinical feasibility of accelerated synthetic MR imaging with deep learningbased reconstruction in pediatric neuroimaging and to investigate the impact of deep learning-based reconstruction on image quality and quantitative values in synthetic MR imaging. MATERIALS AND METHODS:This study included 47 children 2.3-14.7 years of age who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…Measurement of image SNR by two readers also indicated that TSE-DL had improved SNR compared with TSE-SD. These results are consistent with previous studies [ 13 , 18 , 19 ]. For instance, Bash et al [ 13 ] enrolled 61 patients undergoing lumbar spine MRI and found that the SNR of fast DL imaging sequences was better than that of standard sequences.…”
Section: Discussionsupporting
confidence: 94%
“…Measurement of image SNR by two readers also indicated that TSE-DL had improved SNR compared with TSE-SD. These results are consistent with previous studies [ 13 , 18 , 19 ]. For instance, Bash et al [ 13 ] enrolled 61 patients undergoing lumbar spine MRI and found that the SNR of fast DL imaging sequences was better than that of standard sequences.…”
Section: Discussionsupporting
confidence: 94%
“…To our knowledge, this is the first application of the evaluation of AIR DLR in both MLGE and PSLGE with different NR levels. Our results are consistent with those of previous studies in which AIR DLR obtained better image quality compared to the conventional reconstruction method (2327). The subtracted images also showed that DLR is effective in reducing noise and truncating artifacts.…”
Section: Discussionsupporting
confidence: 93%
“…The visual evaluation of myelin development based on image signal intensity in conventional MRI is imprecise, and the quantitative evaluation of myelin development using diffusion tensor imaging, magnetic resonance spectroscopy, and other imaging techniques requires a long scanning time. SyMRI can quantitatively analyze the T1, T2, and PD values of the whole brain in a single scanning session, which provides a new approach to the detection and monitoring of myelin developmental abnormalities [ 23 ].…”
Section: Discussionmentioning
confidence: 99%